Quantification of epi- and pericardial adipose tissue deposits between males and females during cardiac CT may potentially help categorize coronary artery disease risk with thoracic circumference. Issue 3 (August 2021) - El-Merhi, F.; Ghieh, D.; Taleb, H.; Abchee, A.; Karout, L.; Saade, C.
Abstract: Introduction: This study aims to investigate the association between epi- and pericardial adipose tissue deposits around the heart against patient body habitus when using cardiac computed tomography (CT). Methods: Ninety-two consecutive patients with suspected coronary artery disease underwent coronary CT angiography with quantitative cardiac and adipose tissue volume measurements. Body mass index (BMI), body surface area (BSA), thoracic circumference, anteroposterior diameter, cardiac and adipose tissue volumes were compared between genders by employing Pearson's correlation and results were considered statistically significant if p  ≤ 0.05. Results: Statistically significant differences between genders were observed with males having a greater height (males 1.72 ± 0.11), BMI (30.76 ± 7.87 kg/m 2 ), BSA (2.06 ± 0.21 m 2 ), thoracic circumference (1022.12 ± 97.90 mm 2 ), and pericardial adipose tissue volume (46.72 ± 36.62 mm 3 ) (p < 0.05). For men, for Group 1 (BMI ≤ 27) each of the measured volumes showed moderate correlation between pericardial adipose tissue and AP chest-diameter ( r  =  0.429, p < 0.05 ), whereas in Group 2 (27 < BMI ≤ 31.1), coronary artery volume had a strong association with the AP chest-diameter (r = 0.453, p < 0.05). Conclusion: BMI and thoracic circumference are closely related to variable epi- and pericardial adipose tissue volumes in both males and females during cardiac CT. Implications for practice: Quantification of epi- and pericardial adipose tissue deposits between males and females during cardiac CT may help further categorise coronary artery disease risk when including BMI and thoracic circumference for males and females.